(untitled) - Calvo, Andres (Berkeley, CA, 2015)
This book is very practical and contains many examples that not only show you how to write code for Glass and Android Wear, but also demonstrate how to apply this code in the context of an app.
Keywords: Android (Nguồn tài nguyên điện tử),Ứng dụng phần mềm,Android (Electronic resource),Wearable computers.,Application software; Phát triển,Development